FORMATION OF PHYSICAL EDUCATIONAL STUDY AND PROFESIONAL SCHOOL IN SLOVENIA, NOWADAY FACULTY OF SPORT - Tomaž Pavlin; Milan Žvan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Physical Education (PE) as new profesion based on physical activity entered in Slovenian and south slavic millieu in the second half of 19 th century. The roots are in gymnastic societies and paralelly in school system. In austrian part of Habsburg Empire in 1869 new school's law was adopted. It proclaimed 2 obligatory hours of PE. With institunalization of PE soon arrised the problem of profesional PE staff and opened the question of profesional physical educational courses or even study for PE trainers and teachers. The problem was firstly solving or by gymnastic courses or later with establishment of special high schools for physical education. In Slovenia important steps in solving the PE profesional problem were done after the second world war by organising new PE study. Despite stereotypes of nonacademism or nonscientism PE gained political and social suport and in the fithtieth of 20. Century Institut for PE was established. Institut was the begginer of High School for Physical Culture, established in 1960. The purpose of new School was to educate and prepare profesionals of PE for the needs of school system and civil-society. On the other side, the establishmet meant also the start of new science - kinesiology. In the paper we will on the basis of sources focused on cruical steps in the process of the educational institutionalization of PE and formation of Faculty of Sport, which in 2010 celebrated its 50 th anniversary.